Evidence for an association of prenatal exposure to particulate matter with clinical severity of Autism Spectrum Disorder - Santos, João Xavier; Sampaio, Pedro; Rasga, Célia; Martiniano, Hugo; Faria, Clarissa; Café, Cátia; Oliveira, Alexandra; Duque, Frederico; Oliveira, Guiomar; Sousa, Lisete; Nunes, Ana; Vicente, Astrid Moura (Environmental research, 2023)
Early-life exposure to air pollutants, including ozone (O3), particulate matter (PM2.5 or PM10, depending on diameter of particles), nitrogen dioxide (NO2) and sulfur dioxide (SO2) has been suggested to contribute to the etiology of Autism Spectrum Disorder (ASD). In this study, we used air quality monitoring data to examine whether mothers of children with ASD were exposed to high levels of air pollutants during critical periods of pregnancy, and if higher exposure levels may lead to a higher clinical severity in their offspring. We used public data from the Portuguese Environment Agency to estimate exposure to these pollutants during the first, second and third trimesters of pregnancy, full pregnancy and first year of life of the child, for 217 subjects with ASD born between 2003 and 2016. These subjects were stratified in two subgroups according to clinical severity, as defined by the Autism Diagnostic Observational Schedule (ADOS). For all time periods, the average levels of PM2.5, PM10 and NO2 to which the subjects were exposed were within the admissible levels defined by the European Union. However, a fraction of these subjects showed exposure to levels of PM2.5 and PM10 above the admissible threshold. A higher clinical severity was associated with higher exposure to PM2.5 (p = 0.001), NO2 (p = 0.011) and PM10 (p = 0.041) during the first trimester of pregnancy, when compared with milder clinical severity. After logistic regression, associations with higher clinical severity were identified for PM2.5 exposure during the first trimester (p = 0.002; OR = 1.14, 95%CI: 1.05–1.23) and full pregnancy (p = 0.04; OR = 1.07, 95%CI: 1.00–1.15) and for PM10 (p = 0.02; OR = 1.07, 95%CI: 1.01–1.14) exposure during the third trimester. Exposure to PM is known to elicit neuropathological mechanisms associated with ASD, including neuroinflammation, mitochondrial disruptions, oxidative stress and epigenetic changes. These results offer new insights on the impact of early-life exposure to PM in ASD clinical severity. •Integration of air pollution data with clinical information for 217 ASD-subjects.•Some ASD-subjects show PM2.5 and PM10 exposure levels above admissible thresholds.•ASD severity linked to PM2.5 exposure during first trimester and full pregnancy.•ASD severity associated with PM10 exposure during third trimester of pregnancy.•PM exposure has been linked to ASD-related neuropathological mechanisms.